Exploring The Adaptability of CEFR Descriptors in The Construction of EFL Reading Test Specifications in Indonesian - Hoinbala, Festif Rudolf; Marpaung, Tiarma (Institut Agama Islam Negeri Palopo, 2025)
The implementation of the Common European Framework of Reference (CEFR) has become a global benchmark in language education, yet its contextual adaptability remains a critical issue, particularly in non-European settings such as Indonesia. This study investigates how CEFR descriptors can be systematically adapted to construct reading test specifications aligned with the learning objectives of EFL reading courses in an Indonesian university context. Focusing on the English Education Study Program at Universitas Kristen Artha Wacana, the researchers employed a qualitative descriptive approach through document analysis of three core reading course syllabi: Intensive Reading 1, Intensive Reading 2, and Extensive Reading. Instructional objectives from these syllabi were mapped against four CEFR reading descriptor scales to determine alignment with proficiency levels ranging from A2 to B2. The researchers then designed test specifications based on these alignments and validated them through expert judgment involving two language assessment specialists. A structured validation checklist was used to assess construct relevance, task appropriateness, text length, and micro-skill inclusion. The findings demonstrated a logical progression of reading proficiency across the courses and confirmed that CEFR descriptors can be meaningfully adapted to the Indonesian EFL context. While the study provides a foundational model for CEFR-aligned reading assessment, it acknowledges limitations related to scope, piloting, and generalizability. Future studies are recommended to conduct empirical trials and explore the integration of digital assessment tools. This research offers practical implications for EFL lecturers and curriculum developers seeking to improve language assessment practices in Indonesian higher education.